Assessment of Neck Circumference Measurement among Type 2 Diabetic Patients in Identifying: Obesity and the Likelihood of Developing Metabolic syndrome. - Hasan, Hayder Sabah (AL-Kindy College Medical Journal, 2012)
Background: Obesity is an evolving major health problem in both developed and developing countries. Traditional obesity indices as body mass index, waist circumference, waist-hip-ratio are well known measures to identify obese subjects, however, neck circumference as an index of upper-body obesity was found to be a simple and time-saving screening measure that can be used to identify obesity and the likelihood of developing metabolic syndrome in type 2 diabetic patients. Aim: to investigate the relationship of neck circumference (NC) to obesity and metabolic syndrome in Iraqi subjects with type 2 diabetes. Methods: The study group included 90 type 2 diabetic subjects (48 men and 42 women) aged 30-68 years. The subjects were those who attending The Specialized Center for Endocrinology and Diabetes/Baghdad. Main indicators studied included Neck Circumference (NC), waist circumference (WC), waist-to-hip ratio (WHR), body mass index (BMI), blood pressure, fasting blood glucose, and lipoprotein levels. Results: Pearson’s correlation coefficients indicated a significant association between NC and body circumference, and waist-hip-ren and from 0.014 to less than 0.0001 in women). Also NC is positively correlated with systolic blood pressure (SBP), diastolic blood pressure (DBP), triglycerides (TGA), fasting blood glucose level (p value from 0.092 to less than 0.0001). Cross tabulation between NC and BMI indicated that NC identified obese persons with 100% sensitivity in men and 90% in women, also a cross tabulation between NC and metabolic syndrome indicated that NC can identify metabolic syndrome with 100% sensitivity in both men and women. Metabolic syndrome was identified according to a modified criteria proposed by the National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATPIII). mass index, waist atio (p <0.0001 in m Conclusion: Neck circumference is positively correlated with BMI, waist circumference, waist-hip-ratio, and positively correlated with components of metabolic syndrome in Iraqi individuals with type 2 diabetes. Accordingly, the measurement of neck circumference could be useful in clinical screening for obese persons and for persons who are at risk of developing metabolic syndrome.